HUBUNGAN KARAKTERISTIK INDIVIDU DENGAN KELUHAN GANGGUAN KULIT PADA PEMULUNG SAMPAH DI TPA TEMESI - Ni Putu Ardiyanti; I Kadek Dwi Arta Saputra; Ni Putu Indah Rosita (Jurnal Cakrawala Ilmiah, 2023)
In the Temesi final garbage dump area, there are many waste pickers with different individual characteristics, waste pickers at the Temesi landfill are people whose job is to select, pick up, and collect waste or used goods that can still be used, based on the observations that the author made, many of the waste pickers who worked were found not to use personal protective equipment and did not attach importance to safety and health aspects. This study used a quantitative research design with a cross-sectional analytical approach. This study was conducted at the Temesi Gianyar Bali landfill, the number of samples in this study was 35 scavengers. The measuring tools and methods used in this study are research questionnaires that have been modified and tested for validity and reliability. In this study, data analysis was carried out in the form of univariate analysis to describe the characteristics of the study and bivariate analysis, with the Chi-square test. The results of this study obtained the results that respondents who felt complaints of skin disorders were as many as 27 people (77.1%), while the proportion of subjective complaints of skin disorders was significantly higher in working period ≥ 5 years with a value of p = 0.047, length of ≥ 8 hours with a value of p = 0.043, use of PPE with an incomplete category with a value of p = 0.000 and personal hygiene with a bad category with a value of p = 0.000. This study conclude, the respondents characteristics were related to complaints of skin damage in scavengers at the Temesi landfill.